Patterns of Bacterial and Archaeal Gene Expression through the Lower Amazon River - Satinsky, Brandon M.; Smith, Christa B.; Sharma, Shalabh; Ward, Nicholas D.; Krusche, Alex V.; Richey, Jeffrey E.; Yager, Patricia L.; Crump, Byron C.; Moran, Mary Ann (Frontiers in Marine Science, 2017)
Analysis of metatranscriptomic and metagenomic datasets from the lower reaches of the Amazon River between Óbidos and the river mouth revealed microbial transcript and gene pools dominated by Actinobacteria, Thaumarchaeota, Bacteroidetes, Acidobacteria, Betaproteobacteria, and Planctomycetes. Three mainstem stations spanning a 625 km reach had similar gene expression patterns (transcripts gene copy-1) across a diverse suite of element cycling genes, but two tributary-influenced stations at the mouth of the Tapajós River and near the Tocantins River at Belém had distinct transcriptome composition and expression ratios, particularly for genes encoding light-related energy capture (higher) and iron acquisition and ammonia oxidation (lower). Environmental parameters that were useful predictors of gene expression ratios included concentrations of lignin phenols, suspended sediments, nitrate, phosphate, and particulate organic carbon and nitrogen. Similar to the gene expression data, these chemical properties reflected highly homogeneous mainstem stations punctuated by distinct tributary-influenced stations at Tapajós and Belém. Although heterotrophic processes were expected to dominate in the lower Amazon, transcripts from photosynthetic bacteria were abundant in tributary-influenced regions, and transcripts from Thaumarcheota taxa genetically capable of chemosynthetic ammonia oxidation accounted for up to 21% of the transcriptome at others. Based on regressions of transcript numbers against gene numbers, expression ratios of Thaumarchaeota populations were largely unchanged within the mainstem, suggesting a relatively minor role for gene regulation. These quantitative gene and transcript inventories detail a diverse array of energy acquisition strategies and metabolic capabilities for bacteria and archaea populations of the world’s largest river system.